2017
DOI: 10.1002/jcb.26144
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Growth Hormone Receptor Trp169Arg Heterozygous Mutation in a Child With Short Stature

Abstract: Mutations in the growth hormone receptor (GHR) gene can cause disruption of the growth hormone signaling pathway, resulting in growth deficiency due to growth hormone (GH) resistance. Both recessive and apparently dominant mutations have been described in the literature. In order to shed some light on the molecular mechanism of partial growth hormone resistance caused by heterozygous mutations, we performed an in-depth in silico analysis of a mutation found in a girl with a previous diagnosis of idiopathic sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Mutations in the GHR gene can alter the ability of GHR to interact with the GH peptide [ 8 ]. Nearly 30 GHR mutations have been reported to be associated with disturbing the GH–GHR combination ( Table 1 and Table 2 ).…”
Section: Ghr Polymorphisms and Individual Dwarfismmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the GHR gene can alter the ability of GHR to interact with the GH peptide [ 8 ]. Nearly 30 GHR mutations have been reported to be associated with disturbing the GH–GHR combination ( Table 1 and Table 2 ).…”
Section: Ghr Polymorphisms and Individual Dwarfismmentioning
confidence: 99%
“…In this axis, as an essential cytokine, GHR introduces the GH signal into the cell and then regulates the expression of IGFs, thereby regulating individual growth. Hence, the expression level and normal functioning of GHR in cells and tissues directly affects the physiological effects of GH [ 7 , 8 ]. Individuals with dysfunctional GHR, experiencing a loss or an abnormality in the GHR response to GH, are extremely short.…”
Section: Introductionmentioning
confidence: 99%
“…In general, slight phenotypic effects of wt/- in autosomal recessive diseases cannot be excluded [ 28 ]. Mono-allelic likely pathogenic variants in proteins with structural similarity to LEP/LEPR are known, comparable to variants in growth hormone [ 29 ], growth hormone receptor [ 30 ], and G-CSF receptor [ 31 ]. In one study of Farooqi et al, LEP wt/- showed lower leptin levels and increased prevalence of obesity than controls [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, to improve the accuracy of the predictions, other techniques, such as molecular dynamics, can be used [21]. This approach has been used by our group to study other mutations related to peptide hormones, such as guanylin [22], uroguanylin [23], lymphoguanylin [24] and growth hormone receptor [25]. Here we show that the rare mutations in mature amylin caused by SNPs are located in conserved position, maintaining the aggregation potential and a similar structure conformation to the wild-type after an unfolding dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Then, to improve the accuracy of predictions, other techniques, such as molecular dynamics, can be used [21]–[25]. This approach has been used by our group to study other mutations related to peptide hormones, such as guanylin [26], uroguanylin [27], lymphoguanylin [28] and growth hormone receptor [29]. Our hypothesis is that mutations in the amylin gene can alter the peptide structure.…”
Section: Introductionmentioning
confidence: 99%